Assessment off dyslipidemia in pre-diabetic patients with cerebral infraction - Nguyen, Tran Thua; Dang, Tran Huu; Van, Ly Thi Thu; The, Le Trung (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
None.